2022
DOI: 10.1002/ptr.7576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Qishen granules on isoproterenol‐induced chronic heart failure in rats evaluated by comprehensive metabolomics

Abstract: Qishen granules (QSG), a Chinese herbal formula, has been widely used in the treatment of myocardial ischemic chronic heart failure (CHF) for many years, but its mechanism of action is still unclear. In this study, comprehensive metabolomics was used to investigate the underlying protective mechanisms of QSG in an isoproterenolinduced CHF rat model. A total of 14 biomarkers were identified in serum and 34 biomarkers in urine, which were mainly related to fatty acid metabolism, bile acid metabolism, amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…High-throughput mass spectrometry-based metabolomics has been used to investigate the underlying mechanisms of Qishen granules on myocardial ischemic chronic heart failure and revealed that Qishen granules might alleviate amino acid metabolism disorders by regulating endogenous metabolites [145]. UPLC/MS metabolomics analysis revealed that the Hu'po Anshen decoction regulated the abnormalities of glucose-alanine and malate-aspartate shuttle to promote bone formation [146].…”
Section: Multi-target and Effect Mechanism Exploration Of Herbal Medi...mentioning
confidence: 99%
“…High-throughput mass spectrometry-based metabolomics has been used to investigate the underlying mechanisms of Qishen granules on myocardial ischemic chronic heart failure and revealed that Qishen granules might alleviate amino acid metabolism disorders by regulating endogenous metabolites [145]. UPLC/MS metabolomics analysis revealed that the Hu'po Anshen decoction regulated the abnormalities of glucose-alanine and malate-aspartate shuttle to promote bone formation [146].…”
Section: Multi-target and Effect Mechanism Exploration Of Herbal Medi...mentioning
confidence: 99%
“…Qishen Granule can regulate the production of UDCA, glycodeoxycholic acid, and other BAs in the rat model of HF. [ 74 ] Figure 5 displays the role of Chinese medicine in treating HF by regulating BAs.…”
Section: Traditional Chinese Medicine (Tcm) Treats Hf By Regulating G...mentioning
confidence: 99%